Brother Jonathan Runs for President: Spoof Campaigns, the Janus Laugh, and the Rise of Donald Trump - Yaross Lee, Judith (AMERICANA E-journal of American Studies in Hungary, 2023)
Since the 1830s, mock-campaigns for President of the United States have featured comic candidates descended from Brother Jonathan, the eighteenth-century folk figure who characterizes the ordinary American as the quintessential democratic citizen. Jonathan’s rustic innocence and virtue distinguish him from the corrupt politicians who arise from the elite, and thereby contribute to the two-faced joke—the Janus Laugh—underlying the past century’s many spoof campaigns: elitism in the form of populism. Via the reverse logic of irony and humor, nominations for unlikely spoof candidates endorse the status quo of seasoned politicians by implying that the alternative to elite leadership is a joke. Donald Trump’s 2016 candidacy demonstrates that the ideology of spoof campaigns also animates authentic runs for American political office.